PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. PLN (PERSERO) ULP KECAMATAN SAPE KABUPATEN BIMA - Salahudin, Suharni; Anwar Ramli; Agung Widhi Kurniawan (STIE-PMCI, 2022)
This study aims to determine the influence of leadership and work motivation on employee performance at PT. PLN (Persero) ULP, Sape District, Bima Regency. The variables in this study are 3 independent variables (X) namely Leadership and Work Motivation while the dependent variable (Y) Employee Performance is measured by using data from a questionnaire (primary) to related parties. The population of this study are all employees who work at PT. PLN (Persero) ULP Sape while the sample consisted of 60 people. The analytical technique used is the validity test, the reliability test, the multiple regression analysis of the coefficient of determination (R2), the f TEST and the T test with the help of SPSS 24 computer software. The results of the study show that partially the leadership variable (X1) and work motivation variable (X2) have a positive and significant influence on employee performance (Y). Simultaneously the two independent variables, namely leadership (X1) and work motivation (X2) have a positive and significant effect on the dependent variable, namely employee performance (Y).